Perancangan Sistem Reservasi Berbasis Website Pada Lubana Sengkol Outbound Setu Dengan Metode Agile - Ibadi Muchlis; Muhammad Baihaqi Hasan; Roeslan Djutalov (CV. Multi Kreasi Media, 2024)
Lubana Sengkol Outbound, which is located in Setu, is a business sector engaged in tourism, as well as restaurants and swimming pools. This research found a problem which still uses a manual reservation system. So we found a problem, which is still doing the reservation system manually in serving customers, so delays in serving often occur. Therefore, by using the Agile method, researchers try to analyze and implement a website-based sales system that is connected to a database so that everything runs more easily, and buyers will be served faster when they want to buy. With this website-based information system, it makes it easier for companies to find out the remaining schedules that have been reserved and schedules that are still empty. The absence of an information system in managing schedules is an obstacle that companies have in selling their services. To overcome this problem, an information system is needed that can be accessed by employees to manage the sale of their services and also a website application that can be accessed by customers to get information about the services offered. With the application made on Lubana Sengkol Outbound, it can shorten the reservation time because customers no longer need to come directly to the place.